SCOUT – Sarcoidosis Outcomes Taskforce. A systematic review of outcomes to inform the development of a core outcome set for pulmonary sarcoidosis - Harman, Nicola; Gorst, Sarah; Williamson, Paula; Barnathan, Elliot; Baughman, Robert; Judson, Marc; Junk , Heidi; Kampstra, Nynke; Sullivan, Eugene; Victorson, David; Walton, Marc; AL-Hakim, Tamara; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
BackgroundClinical trials evaluating different management strategies for pulmonary sarcoidosis may measure different outcomes. This heterogeneity in outcomes can lead to waste in research due to the inability to compare and combine data. Core outcome sets (COS) have the potential to address this issue and here we describe a systematic review of outcomes as the first step in the development of a COS for pulmonary sarcoidosis research.Methods: A search of clinical trial registries for phase II, III and IV trials of pulmonary sarcoidosis was undertaken along with a rapid review of the patient perspective literature.  Each study was screened for eligibility and outcomes extracted verbatim from the registry entry or publication then reviewed, grouped and categorised using the COMET taxonomy.   Results: 36 trial registry entries and 6 studies on patients’ perspective of pulmonary sarcoidosis were included reporting 56 and 82 unique outcomes respectively across 23 domains. The most frequently reported outcome domain was “respiratory, thoracic and mediastinal outcomes”. However, the patients’ perspective literature identified outcomes in the “personal circumstances” and “societal/carer burden” domains that were not reported in any of the included trial registrations.Conclusions:  Using both clinical trial registry data and published literature on patients’ perspective has allowed rapid review of outcomes measured and reported in pulmonary sarcoidosis research. The use of multiple sources has led to the development of a comprehensive list of outcomes that represents the first step in the development of a COS for use in future pulmonary sarcoidosis research.